PERKEMBANGAN ORGANISASI DAN MANAJEMEN PEMERINTAH DESA STUDI KASUS DI KABUPATEN LEBAK PROVINSI BANTEN - Rusito Rusito (Jurnal Administrasi Publik, 2017)
With village autonomy and decentralization patterns, the development of village government organizations and management must be increased so that the actual goals of village autonomy that are to improve the welfare of the community are quickly achieved. However, the condition that the development of the organization and management of the village government is still very slow to go to the village government to serve. The purpose of this paper is to gain an understanding of the development of village government management organizations with case studies in Lebak District of Banten Province. The framework used is thinking of Janet V Denhart et al (2007: 121).The conclusion of this paper is that the development of the organization and management of the village government in the study object begins with the abandonment of past village government and has formally entered the village bureaucracy government. Only a small percentage of village governments enter into the village government entrepreneurship phase because of the lack of entrepreneurial spirit. Village government serves with a vengeance is plagued by factors of geographical area and difficulties even though village budgets from the government are increasing.